Diversity and Emotion: The New Frontiers in Organizational Behavior Research - Ashkanasy, Neal M.; Härtel, Charmine E.J.; Daus, Catherine S. (Journal of Management, 2002)
This article provides a review of recent developments in two topical areas of research in contemporary organizational behavior: diversity and emotions. In the section called “Diversity,” we trace the history of diversity research, explore the definitions and paradigms used in treatments of diversity, and signal new areas of interest. We conclude that organizational behavior in the 21st century is evolving to embrace a more eclectic and holistic view of humans at work. In the section called “Emotions,” we turn our attention to recent developments in the study of emotions in organizations. We identify four major topics: mood theory, emotional labor, affective events theory (AET), and emotional intelligence, and argue that developments in the four domains have significant implications for organizational research, and the progression of the study of organizational behavior. As with the study of diversity, the topic of emotions in the workplace is shaping up as one of the principal areas of development in management thought and practice for the next decade. Finally, we discuss in our conclusion how these two areas are being conceptually integrated, and the implications for management scholarship and research in the contemporary world.